Adopsi E-Commerce Dalam Mendukung Perkembangan Usaha Mikro Kecil Dan Menengah (UMKM) Di Masa Pandemi Covid-19 - Adriani Kala'lembang (UNIVERSITAS PGRI MADIUN, 2020)
The Covid-19 pandemic struck Indonesia and also the rest of the world, which has a huge impact in the Micro, Small and Medium Enterprises (MSMEs). It is necessary to have a big movement to revive the economic passion in Indonesia, especially MSMEs, one of which is by utilizing e-commerce. This paper presents a conceptual framework for adopting e-commerce. Based on the results of a review of several articles, it was concluded that three factors could be used to adopt e-commerce, including, organizational characteristics, environmental characteristics, and leadership characteristics. To test the benefits and ease of using e-commerce, it can use the Technology Acceptance Model (TAM) theory.